Letter : Foodstuffs for Spain - Schevenels, Walther, b. 1894
029-0074-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe IFTU Sch/H TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter No. 20th December, 1937. Mr W. M. Citrine, LONDON. Dear Comrade Citrine, FOODSTUFFS FOR SPAIN We note what you say, in your letter of the 18th December under this heading, about difficulties in the sailing of the s.s. "Hartbridge", and will await definite news of the ship having left England before we communicate again with our comrades in Barcelona. Yours sincerely, W. Schevenels, General Secretary: 292/946/29/74